HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN KUALITAS KEHIDUPAN KERJA PADA KARYAWAN DI PT. LUMINA PACKAGING SIDOARJO - Sinta Khusnullia; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2021)
Abstract This study aims to determine the relationship between organizational climate with quality of work life in employee PT. Lumina Packaging Sidoarjo. The method used in this research is quantitative research methods. The sampling technique ued in this study was purposive sampling technique which involved 116 employees. The instruments used in this study were the scale of organizational climate and the scale of the quality of work life. Data analysis used is analysis of product moment correlation. The coefficient value generated based on the analysis of the results that has been carried shows a value of 0,496 (r=0,496) with a significance level of 0,000 (p<0,05), which means that the proposed hypothesis is acceptable, there is a significant relationship between organizational climate and the quality of work life of employees in PT. Lumina Packaging Sidoarjo. Keywords: organizational climate, quality of work life, employee